ANTI-MAGIC LABELING FOR CERTAIN GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
Graph theory is the study of graphs, which are statistical structures, used to representation of pair wise relations between objects. Graph theory is applicable to examine artifact that is connected to other things. Some complicated problems formulate easy solutions when characterized as a graph. A graph in this statement is made up of nodes called as vertices and connections between the vertices called as edges. Generally vertices and edges of a graph are referred as graph elements. Graph theorists are progressively discovering that abundance of their problems can be resolved, or their research furthered by the use of computing techniques. Graph labeling problems are one among them. Numerous variations of labeling have been investigated in the literature. A complete survey on contemporary results, speculation and open problems in labeling graph is presented by J.A.Gallian[1]